A bibliometric and systematic review: Linking land use and land cover (LULC) change prediction with soil degradation - Dewi, Citra; Kusumastuti, Dyah Indriana; Yuwono, Slamet Budi; Wahono, Endro Prasetyo (Brawijaya University, 2026)
Changes in land use and land cover (LULC) are among the main drivers of soil degradation, especially in urban areas under strong development pressure. The lack of land in urban areas often pushes development toward ecologically sensitive areas, such as hillslopes and riverbanks. These practices may alter soil biophysical characteristics and accelerate local-scale environmental degradation. Accordingly, predicting land-use and land-cover change is vital for assessing the potential risk of future soil degradation. Many spatial modeling methods have been developed to predict LULC change dynamics; however, their association with soil quality degradation has yet to be systematically illustrated in the scientific literature. Research on LULC change prediction and its implications for soil quality degradation is widely scattered across the scientific literature. This review conducted a literature search of the Scopus database and analyzed the research trends, methodological approaches, and the relationship between land cover change and soil quality degradation. The review results showed that LULC change is consistently linked to subsequent declines in soil characteristics, such as soil organic carbon, erosion, and soil structural stability. These results underscore the need for predictive models as valuable tools for anticipating soil degradation risks and guiding sustainable land use planning.